Apoptosis Inhibitor of Macrophages in Cats: A Potential Link Between an Exon 3 Variant Allele and Progression of Naturally Occurring Chronic Kidney Disease - Gabriela C. L. Evangelista; Julianne K. Hwang; Liam E. Broughton‐Neiswanger; Emily C. Carlo Reis; Michael H. Court; Katrina A. Mealey; Nicolas F. Villarino (Journal of Veterinary Internal Medicine)
ABSTRACT Background The protein apoptosis inhibitor of macrophages (AIM) is involved in kidney repair. An AIM (fAIM) genetic variant in cats resulting in a domain duplication might abrogate fAIM's protective effect on kidney function. Objectives To confirm that the domain duplication previously described in fAIM results from an exon duplication at the genomic level and to determine if cats with chronic kidney disease (CKD) harboring the variant fAIM allele are at higher risk for a decline in renal function relative to fAIM wild‐type cats. Animals Medical records (n = 172) and genomic DNA samples (n = 100) from cats presented to Washington State University and having a diagnosis of CKD were analyzed. Methods Sequencing and PCR were used to determine fAIM genotype. Based on serum creatinine (SCr) concentrations, cats were phenotyped according to IRIS CKD staging. The phenotype–genotype association was tested using Fisher's exact test. Results The 4‐domain variant of fAIM was confirmed to be a result of exon 3 duplication and is present in 62% of the DNA samples from cats. Medical records of cats (n = 50) with CKD met the inclusion criteria. Cats homozygous for the exon 3 fAIM variant allele are more likely to have worse IRIS stage (p = 0.01) and more likely to have experienced renal function deterioration (increasing SCr concentration) than fAIM wild‐type cats (p = 0.03). Conclusions and Clinical Importance The fAIM homozygous variant genotype is associated with declining kidney function in cats with CKD, presumably from deficient fAIM‐mediated renal tubular repair.